1999
DOI: 10.1103/physreve.60.3425
|View full text |Cite
|
Sign up to set email alerts
|

Traveling time and traveling length in critical percolation clusters

Abstract: We study traveling time and traveling length for tracer dispersion in two-dimensional bond percolation, modeling flow by tracer particles driven by a pressure difference between two points separated by Euclidean distance r. We find that the minimal traveling time t(min) scales as t(min) approximately r(1.33), which is different from the scaling of the most probable traveling time, t* approximately r(1.64). We also calculate the length of the path corresponding to the minimal traveling time and find l(min) appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 12 publications
5
106
0
1
Order By: Relevance
“…In the current adaptation to generate the saturation dependence of the dispersion, we had to make the calculations suitable for structural percolation controls, i.e., direct topological constraints. The theoretical development is strongly influenced by work of the Eugene Stanley group [59], which shows that characteristic system crossing times scale with system length to the fractal dimensionality of the backbone, D b . We did not use the scaling function for arrival times used in [59] and related publications, however.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current adaptation to generate the saturation dependence of the dispersion, we had to make the calculations suitable for structural percolation controls, i.e., direct topological constraints. The theoretical development is strongly influenced by work of the Eugene Stanley group [59], which shows that characteristic system crossing times scale with system length to the fractal dimensionality of the backbone, D b . We did not use the scaling function for arrival times used in [59] and related publications, however.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical development is strongly influenced by work of the Eugene Stanley group [59], which shows that characteristic system crossing times scale with system length to the fractal dimensionality of the backbone, D b . We did not use the scaling function for arrival times used in [59] and related publications, however. That distribution was proposed for use in a binary medium, in which the constituents are either highly, or weakly, permeable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this article was written we have learned of a paper by Lee et al [122] in which it is shown that the scaling of time with Euclidean length is governed by the mass fractal dimensionality of the backbone cluster, and this should be used to calculate an effective tortuosity. Numerical results show agreement with relevant simulations for two-dimensional diffusionless dispersion by Liu et al [123].…”
Section: Notesmentioning
confidence: 99%